Genetically Engineered Vaccinia Viruses As Agents for Cancer Treatment, Imaging, and Transgene Delivery - Haddad, Dana (Frontiers in Oncology, 2017)
Despite advances in technology, the formidable challenge of treating cancer, especially if advanced, still remains with no significant improvement in survival rates, even with the commonest forms of cancer. Oncolytic viral therapies have shown great promise for the treatment of various cancers, with the possible advantages of stronger treatment efficacy compared to conventional therapy due to higher tumor selectivity, and less toxicity. They are able to preferentially and selectively propagate in cancer cells, consequently destroying tumor tissue mainly via cell lysis, while leaving noncancerous tissues unharmed. Several wild type and genetically engineered VACV strains have been tested both in preclinical and clinical trials with promising results. Greater understanding and advancements in molecular biology has enabled the generation of oncolytic viruses genetically engineered for safer and more efficacious treatment, including arming VACVs with cytokines and immunostimulatory molecules, anti-angiogenic agents, and enzyme pro-drug therapy, in addition to combining VACVs with conventional external and systemic radiotherapy, chemotherapy, immunotherapy and other virus strains. Furthermore, novel oncolytic vaccinia virus strains have been generated that express reporter genes for the tracking and imaging of viral therapy and monitoring of therapeutic response. Further study is needed to unlock VACV’s full potential as part of the future of cancer therapy.